The Development of Golden pompano (Trachinotus blochii) Thai Sausage Product Mixed with Green Caviars (Caulerpa lentillifera) - Munlum, Satitpong; Suksri, Chaweewan (Journal of Food Technology, Siam University, 2023)
This experimental research aimed to develop Thai Sausage made from Golden Pompano mixed with Green Caviar. The experiment consisted of three major stages: 1) to explore the quantity ratios of Golden Pompano per pork during the production process: 80:20, 90:10, and 100:0 (based on the weights). According to ten experts, using 100 percent of Golden Pompano per weight obtained the highest overall satisfaction scores. Therefore, this recipe was being selected to mix with Green Caviar. 2) The sausage from previous process was brought to mixed with 0.1, 0.5 and 1.0 percent of Green Caviar respectively. According to the experts, the sausage with 1.0 percent of Green Caviar received the highest satisfaction scores, especially in terms of texture and flavors. 3) The chemical quality, microbiological quality, and nutritional values of the product were experimented. The results showed that the microorganisms occurred during the second week was equivalent to 2.6X104 colonies per 1 gram of sample. Furthermore, the amounts of yeast found in this product was 1.3x103 colonies per 1 gram, which defined that the product’s shelf-life is 2 weeks, if it is stored in a closed container at room temperature. In terms of nutrition, the product was found packed with protein, carbohydrate, fiber, beta-carotene, and essential fatty acids such as palmitoleic, oleic, and linoleic acid.